Rotavirus Vaccine Take in Infants Is Associated With Secretor Status. (24th October 2018) - Armah, George E; Cortese, Margaret M; Dennis, Francis E; Yu, Ying; Morrow, Ardythe L; McNeal, Monica M; Lewis, Kristen D C; Awuni, Denis A; Armachie, Joseph; Parashar, Umesh D
Abstract: Rotaviruses bind to enterocytes in a genotype-specific manner via histo-blood group antigens (HBGAs), which are also detectable in saliva. We evaluated antirotavirus immunoglobulin A seroconversion ('vaccine take") among 166 Ghanaian infants after 2–3 doses of G1P[8] rotavirus vaccine during a vaccine trial, by HBGA status from saliva collected at age 4.1 years. Only secretor status was associated with seroconversion: 41% seroconversion for secretors vs 13% for nonsecretors; relative risk, 3.2 (95% confidence interval, 1.2–8.1; P = .016). Neither Lewis antigen nor salivary antigen blood type was associated with seroconversion. Likelihood of "take" for any particular rotavirus vaccine may differ across populations based on HBGAs. Abstract : Infants who are nonsecretors were about one-third as likely to have a serum antibody response after receiving oral G1P[8] rotavirus vaccine than secretors. Likelihood of "take" for any particular rotavirus vaccine may differ across populations based on histo-blood group antigens.